2023
DOI: 10.3390/medicina59061111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentric-Oriented Strength Training on Return to Sport Criteria in Late-Stage Anterior Cruciate Ligament (ACL)-Reconstructed Professional Team Sport Players

Marko D. M. Stojanović,
Nikola Andrić,
Mladen Mikić
et al.

Abstract: Background and Objectives: An effective post-injury training program is essential to regain performance and fulfill criteria for return to sport for team sport athletes following anterior cruciate ligament (ACL) reconstruction. The aim of this study was to compare the effects of 6 weeks of eccentric-oriented strength training vs. traditional strength training during the late-stage ACL-rehab phase on leg strength and vertical and horizontal jumping performance in professional team sport athletes. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The effectiveness of postoperative rehabilitation is critical for ensuring optimal outcomes following ACL reconstruction. According to a recent study, a 6-week eccentricoriented strength training during the late-stage ACL-rehab phase demonstrated superior leg strength and jump performance for professional team sport athletes compared to traditional strength training [47]. Such findings suggest that the integration of eccentric-oriented strength training, potentially coupled with the benefits of the tubularized graft, might offer a comprehensive approach to expedite recovery and return to sports.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of postoperative rehabilitation is critical for ensuring optimal outcomes following ACL reconstruction. According to a recent study, a 6-week eccentricoriented strength training during the late-stage ACL-rehab phase demonstrated superior leg strength and jump performance for professional team sport athletes compared to traditional strength training [47]. Such findings suggest that the integration of eccentric-oriented strength training, potentially coupled with the benefits of the tubularized graft, might offer a comprehensive approach to expedite recovery and return to sports.…”
Section: Discussionmentioning
confidence: 99%
“…Training with an extended eccentric phase may be a better option for recovery after ACL reconstruction because it provides improved lower limb strength and improved performance in various jump tests. Stojanovic et al [17] showed that a 6-week eccentric training programme produced a significantly greater improvement in lower limb strength than standard strength training. A longer duration of the eccentric phase has proven to be a good method of accelerating rehabilitation or PR as a result of ACL rupture due to unique neural patterns and increased mechanical muscle tension, which provides a better neuromuscular response to strength training.…”
Section: Introductionmentioning
confidence: 99%